Firefighter hose rolling method: Low back pain risks analysis with full-factorial approach - Mohammad Luqman Hakim, Mustapha; Salwa, Mahmood; Helmy Mustafa, El Bakri; Ismail, Abdul Rahman; Mohd Fahmi, Badulrudin; Norazlianie, Sazali (Semarak Ilmu Publishing, 2024)
Firefighters frequently face the risk of Low back pain (LBP) due to the strenuous nature of their duties, especially during hose rolling tasks. Prioritizing their safety and health is vital. This study aimed to evaluate and compare various hose rolling techniques to lower the LBP risk in firefighters. A full-factorial approach was employed to exhaustively examine every possible combination of three key factors: the hose rolling method (conventional, mechanical, motorized), hose condition (dry, wet, dirty), and hose length (10, 20, 30 meters). Across 27 different trials, an Industrial Lumbar Motion Monitor (iLMM) was used to assess the LBP risk, which is lift rate, average twisting velocity, maximum moment, maximum sagittal flexion, and maximum lateral velocity. The study's results indicated that conventional method had the highest LBP risk at 58.22%, with mechanical rolling at 34.33%. In contrast, the motorized hose rolling method showed a significantly lower risk, averaging at 17.44%. This denotes a 40.78% reduction in LBP risk compared to conventional hose rolling method, positioning the motorized roller as the most effective and safest option among those tested. This method's efficacy underscores its potential as a viable solution for improving firefighter safety. These findings offer important insights into occupational health and safety in firefighting. The data suggests that adopting motorized hose rolling tools could significantly alleviate the physical burdens and associated health hazards firefighters face. This advancement is a critical step towards enhancing their overall safety and well-being in the field.